Exploring the Relationship Between Comprehensive Respiratory Assessment and Intra-Extracardiac Biomarkers in Heart Failure Rehabilitation - Triangto, Kevin; Radi, Basuni; Siswanto, Bambang B.; Tambunan, Tresia FU.; Heriansyah, Teuku; Harahap, Alida R.; Kekalih, Aria; Katsukawa, Hajime; Santoso, Anwar (Writing Center IMERI FMUI, 2024)
Introduction: Heart failure with reduced ejection fraction (HFrEF) is well-known as a systemic disease that involves cardiac and extracardiac issues, with respiratory function playing on of the key role in rehabilitation prognosis. Biomarkers such as soluble suppression of tumorigenicity 2 (sST2), myostatin, miRNA-133, and NT-proBNP indicate disease progression. Notably, sST2, which is also produced by the lungs, predicts heart failure outcomes. This study examines the relationship between comprehensive respiratory assessments (e.g., diaphragmatic ultrasonography, spirometry) and intra-extracardiac biomarkers to improve rehabilitation strategies. Methods: Sixty-nine HFrEF patients underwent respiratory evaluations, including diaphragmatic ultrasonography, spirometry, chest expansion measurements, and a six-minute walking test (6MWT). Biomarkers assessed were sST2, myostatin, miRNA-133, and NT-proBNP. Associations between respiratory parameters and biomarkers were analyzed using t-tests and correlation analyses. Results: The median age was 56 years, and 33 (47.82%) of the subjects had diaphragmatic dysfunction, resulting in poorer 6MWT performance (378.03±58.15 m vs 409.75±63.65 m, p=0.017) and other parameters. Superior chest expansion negatively correlated with sST2 (r=−0.387, p=0.001) and positively with miRNA-133 (r=0.442, p<0.001). Similar results were found for inferior chest expansion. No significant correlations were observed for other biomarkers. Conclusion: This study highlights strong associations between chest expansion and sST2/miRNA-133, suggesting that incorporating respiratory assessments and training into HFrEF rehabilitation could enhance outcomes by addressing cardiorespiratory insufficiencies. Given sST2's predictive value for heart failure prognosis, these findings support a multi-component rehabilitation strategy incorporating respiratory training, such as aerobic and inspiratory muscle exercises, to enhance cardiopulmonary outcomes. This integrated approach offers promise for future HFrEF rehabilitation protocols.